Effects of electrical pretreatment conditions on osmotic dehydration of apple slices: Experimental investigation and simulation. (June 2016) - Yildiz, Hasan; Icier, Filiz; Eroglu, Salih; Dagci, Gamze
Abstract: Electrical pretreatments at 9 different conditions consisting of the combination of 3 different voltage gradients (20, 27, and 32 V/cm) and 3 different application times (10, 20, and 30 s) were applied on apple slices. Apple slices were osmotically dehydrated in 50% sucrose solution at 40 °C until their total dry matter content (TDM) reached to 40%. The effect of pretreatment conditions on the change of water loss and solid gain during osmotic dehydration was investigated, and effective diffusion coefficients were determined. The time needed to reach up to 40% TDM content was predicted by using the numeric solution of unsteady state mass transfer equations and diffusion coefficients via MATLAB code written. The electrical pretreatments reduced the osmotic dehydration time by in the range of 26–64%. The final water and solid distributions of apple slices were simulated in ANSYS. Modeling and simulation results were in good agreement with experimental data (p < 0.05). Industrial relevance: Since the electrical pretreatment both shortens the osmotic dehydration time and increases the water removed per unit energy used, its application prior to osmotic dehydration processes in the commercial productions will be economical. The proposed modeling and simulation approach for assessment of the effects of electrical pretreatments on osmotic dehydration characteristics may provide valuable information on the scaling up of these conditions in the industrial scale systems. Highlights: The electrical pretreatment shortened the osmotic dehydration time. The electrical pretreatment increased the water removed per unit energy used. The predicted times were in good agreement with experimental data. The simulation model predicted the solid/water distributions successfully.